Women's satisfaction and symptoms following NovaSure endometrial ablation: A postal questionnaire survey in Lothian, Scotland. (May 2014) - Unger, H. W.; Megaly, E.; Dick, A.; Horne, A. W.; Milne, S.; West, C.
Abstract Impedance-controlled endometrial ablation (NovaSure) is commonly used to treat premenopausal heavy menstrual bleeding in Lothian, Scotland. Using postal questionnaires, we assessed patient satisfaction, treatment success and post-procedure symptoms in a cohort of women who had NovaSure treatment between January 2007 and May 2009. The response rate was 61.2% (115/188): 90.4% (104/115) of women were satisfied and would recommend the procedure; 36.8% (42/114) of women were amenorrhoeic at follow-up (mean = 497 days) and NovaSure significantly improved levels of both menstrual bleeding and pain (p < 0.01). Of the women, 67.0% (77/115) reported symptoms such as discomfort, vaginal discharge and bleeding/spotting within 6 weeks following NovaSure. A total of 13.9% (16/115) required further treatment following NovaSure, including hysterectomy. Patient satisfaction with NovaSure was high. Preoperative counselling needs to include information on character and duration of postoperative symptoms. Future research could compare patient satisfaction and clinical outcomes between NovaSure and the levonorgestrel-releasing intrauterine system.